Pattern recognition of Ficus deltoidea jack varieties through chemometric application - Wan Siti Azierah Wan Mohd Azemin
Ficus deltoidea Jack (FD) is a South East Asia native plant and has been consumed as herbal medicines to treat various diseases. This plant occurs in at least eight varieties in Malaysia namely Ficus deltoidea var. deltoidea (FDD), var. trengganuensis (FDTG), var. kunstleri (FDK), var. motleyana (FDM), var. intermedia (FDI), var. borneensis (FDBN), var. bilobata (FDB) and var. angustifolia (FDA). However, the confusion arises on the identification and therapeutic potential due to the varietal status. This study was performed to establish the pattern recognition of FD varieties through chemometrics application for discrimination within varieties based on chemical fingerprinting. The-techniques used in developing fingerprinting include Fourier Transform Infrared (FTIR), High Performance Thin Layer Chromatography (HPTLC), High Performance Liquid Chromatography (HPLC) and Gas Chromatography-Mass Spectrometry (GC-MS). Quantification of marker contents, vitexin and isovitexin were also carried out by HPTLC and HPLC in of each variety. Antioxidant activity was determined by 2, 2-diphenyl-l-picrylhydrazyl (DPPH) assay and total phenolic content measured by Folin-Ciocalteu methods. Samples were collected from several locations in Peninsular Malaysia and Borneo (Sarawak) and were extracted with methanol and water. Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA) of FTIR, HPTLC and GC-MS data classified FD varieties into different grouping patterns for both extracts. Discriminant Analysis (DA) of FTIR confirmed the three clusters established from HCA grouping for both extracts. While discriminant analysis of HPTLC have merged five and three clusters in HCA grouping of methanol and water extract, respectively into two different groups only. Discriminant analysis of GC-MS also classified three clusters in HCA grouping into two groups for methanol extract. Quantification of vitexin and isovitexin revealed that FD varieties have different marker concentration. FDD was found to contain the highest amount of vitexin and FDBN contained the highest amount of isovitexin for both extract. FDI and FDIW posses the highest antioxidant activity for methanol and water extracts with their ICso values of 50llg/mL and 62Ilg/mL, respectively. On the other hand, FDK and FDIW have the highest content of phenolics compounds. Antioxidant activity and total phenolic content of water extract was correlated with each other but not in methanol extract based on observation of antioxidant activity and phenolic content for both descending trend comparison. Findings from this study indicated that chemometric application was successfully discriminate FD varieties into different pattern based on types of techniques used. The amount of two internal markers, vitexin and isovitexin are valuable to be used as quality control parameter. It also was found that FD varieties have different level of antioxidant activity. The results from this study showed that the varieties of Ficus deltoidea are significantly different from each other and should be carefully selected in order to optimize their benefits. Data obtained in this work can be used in identification, classification and quality control for the standardization of Ficus deltoidea Jack in herbal product development.